The Effect of Paylater System, Financial Literacy and Understanding of Islamic Economics on Consumer Consumption Patterns in E-Commerce (A Case Study of the Community in Colomadu District): Studi Kasus pada Masyarakat di Kecamatan Colomadu - Nurul Munawaroh; Iin Emy Prastiwi; Muhammad Tho’in (ITB AAS INDONESIA Surakarta, 2026)
The development of digital technology has contributed to changes in consumer behavior, particularly through the use of e-commerce and digital financial services such as PayLater. The convenience offered by digital payment systems is assumed to influence consumer consumption patterns. This study aims to examine the effect of PayLater usage, financial literacy, and understanding of Islamic economics on consumer consumption patterns in e-commerce in Colomadu District. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 respondents selected using simple random sampling. The data were analyzed using multiple linear regression preceded by validity, reliability, and classical assumption tests, as well as hypothesis testing using t-test and F-test. The results show that partially, PayLater usage and understanding of Islamic economics do not have a significant effect on consumer consumption patterns. In contrast, financial literacy has a significant effect on consumption patterns. Simultaneously, PayLater usage, financial literacy, and understanding of Islamic economics have a significant effect on consumption patterns. These findings indicate that financial literacy plays a more dominant role in shaping consumer behavior compared to the convenience of digital payment systems and the understanding of Islamic economic values.